Inflammatory biomarkers prior to antiretroviral therapy as prognostic markers of 12-month mortality in South Africa and Uganda. (1st November 2019) - Siedner, Mark J.; Bwana, Mwebesa Bosco; Asiimwe, Stephen; Musinguzi, Nicholas; Castillo-Mancilla, Jose; Amanyire, Gideon; Tracy, Russell P.; Bangsberg, David R.; Orrell, Catherine; Haberer, Jessica E.
Abstract : Objective: The aim of this study was to determine the utility of biomarkers of immune activation, systemic inflammation and coagulopathy prior to antiretroviral therapy to predict mortality during the first year of antiretroviral therapy (ART) in sub-Saharan Africa. Design: A prospective, observational cohort. Methods: We measured soluble CD14, interleukin-6 and D-dimer in nonpregnant individuals initiating ART in South Africa and Uganda in the Measuring Early Treatment Adherence (META) Study. We used survival analysis methods to estimate their association with 12-month mortality, and fit receiver operator curves (ROC) to assess the prognostic value of each biomarker. Results: Six-hundred and sixty individuals were enrolled and had pretreatment biomarkers measured. Approximately 60% were women, with a median CD4 + cell count of 187 cells/μl [interquartile range (IQR) 111–425] and approximately half were enrolled each from South Africa and Uganda. We observed 34 deaths for a crude mortality of 5.3 deaths/100 person-years (py) (95% confidence interval 3.8–7.4), which ranged from 0/100 py to 13.7/100 py in the lowest and highest tertile of pretreatment sCD14, respectively. In Cox models, all three biomarkers were strongly predictive of the hazard of death (adjusted hazard ratio 3–6, all P < 0.01). In multivariable models including biomarkers, both pretreatment CD4 + cell count and pretreatment viral load became borderline or nonsignificantly associated with mortality. The c-statistic for area under ROC was higher for all three biomarkers than for CD4 + cell count ( P < 0.01). Conclusion: Biomarkers of immune activation, systemic inflammation and coagulopathy prior to ART initiation are strongly predictive of early death on treatment after adjustment for CD4 + cell count. Such biomarkers might serve as important prognostic indicators for patient triage in this population. Abstract : Supplemental Digital Content is available in the text